Physiological and Pathological Regulation of Peripheral Metabolism by Gut-Peptide Hormones in Drosophila - Zhou, Xiaoya; Ding, Guangming; Li, Jiaying; Xiang, Xiaoxiang; Rushworth, Elisabeth; Song, Wei (Frontiers in Physiology, 2020)
The gastrointestinal (GI) tract in both vertebrates and invertebrates are now recognized as a major source of signals modulating, via gut-peptide hormones, the metabolic activities of peripheral organs and carbo-lipid balance. Key advances in the understanding of metabolic functions of gut-peptide hormones and their-mediated interorgan communication have been made using Drosophila as a model organism, given its powerful genetic tools and conserved metabolic regulation. Here, we summarize recent studies exploring peptide hormones that are involved in the communication between the midgut and other peripheral organs/tissues during the feeding conditions. We also highlight the emerging impacts of fly gut-peptide hormones on stress sensing and carbo-lipid metabolism in various disease models, such as energy overload, pathogen infection, and tumor progression. Due to the functional similarity of the intestine and its-derived peptide hormones between Drosophila and mammals, it can be anticipated that findings obtained in the fly system will have important implications for the understanding of human physiology and pathology.